2021
DOI: 10.1029/2020jc016893
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime Water Mass Transformation in the Western Iceland and Greenland Seas

Abstract: Hydrographic and velocity data from a 2018 winter survey of the western Iceland and Greenland Seas are used to investigate the ventilation of overflow water feeding Denmark Strait. We focus on the two general classes of overflow water: warm, saline Atlantic‐origin Overflow Water (AtOW) and cold, fresh Arctic‐origin Overflow Water (ArOW). The former is found predominantly within the East Greenland Current (EGC), while the latter resides in the interior of the Iceland and Greenland Seas. Progressing north to sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…2c is likely biased by the large number of summertime hydrographic profiles; also, the re-ventilation process is a relatively new phenomenon. Furthermore, recent studies have demonstrated the importance of lateral processes on the water mass transformation in the EGC 13 , 14 . For example, the ocean response to a cold-air outbreak measured by a joint aircraft-ship campaign in winter 2018 was moderated by lateral advection and mixing near the EGC 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2c is likely biased by the large number of summertime hydrographic profiles; also, the re-ventilation process is a relatively new phenomenon. Furthermore, recent studies have demonstrated the importance of lateral processes on the water mass transformation in the EGC 13 , 14 . For example, the ocean response to a cold-air outbreak measured by a joint aircraft-ship campaign in winter 2018 was moderated by lateral advection and mixing near the EGC 14 .…”
Section: Resultsmentioning
confidence: 99%
“…These latter two currents contribute to the overturning in the high Arctic and also play a fundamental role in the recently documented Arctic Atlantification 37 , 38 . Recent studies have demonstrated that the AW in the EGC, as well as that in the boundary current north of Svalbard in the Amundsen Basin, can be further transformed as a result of reduced ice cover in these regions 13 , 17 , 39 . Hence, it remains unclear how much the reduction in air–sea cooling along the NwAFC might be compensated for by the re-ventilation along the EGC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our observations indicate that, in the interior regime, surface cooling dominated the response with less influence from lateral effects. (We note that isolated eddies shed from the boundary current can modulate the ML response in the interior Iceland and Greenland Seas, as demonstrated by Huang et al ., 2021. )…”
Section: Impacts On the Ocean Mixed Layermentioning
confidence: 98%
“…(1986). It has previously been successfully used to simulate changes in ML properties in the western Nordic Seas (e.g., Moore et al ., 2015; Våge et al ., 2018; Brakstad et al ., 2019; Huang et al ., 2021). Here we use CTD profiles from the base of both survey triangles during the pre‐ and early‐CAO period as initial conditions, and apply atmospheric forcing from ERA5.…”
Section: Impacts On the Ocean Mixed Layermentioning
confidence: 99%
See 1 more Smart Citation